Exiled periphery - Bornman, Nic (School of Architecture, Planning and Geomatics, 2021)
It was a city of unimaginable beauty, where diverse ecological landscapes and people converged to live in harmony. The spatial scenarios were diverse ; the lines separating one ecology from the next, one population group from the next, and urban from vast openness, was universal and apparent. It was a metropolis of extreme contrasts, its inhabitants desired to experience and live within this beauty in an uncontaminated manner, away from the dirt, crime and perversion that was so typical of the city they worked and laboured in. Their homes became spaces of solitude and calm, hermetic retreats where natural beauty could be appreciated. Any attempts from indivi duals or groups, wanting to introduce aspects from the city into their peripheral neighbourhoods, were purged with quick effect, to preserve th i s ideal lifestyle that had been cultivated and not yet become contaminated. The community upheld their duty to protect themselves; collectively they were the guardians of their environments. Life in the suburbs was comfortable. People equipped their homes to minimize the frequency by which they had to travel by car into the city. Typically, the houses had large gardens with swimming pools which simulated the outdoors, and inside there was enough entertainment and electronic devices to keep its inhabitants happy for hours on end. Trips to the local shopping malls happened infrequently, about once a week, but when they did go shopping it was done in large volumes. The home was equipped to accommodate for stock piling, much like an emergency bunker during wartime.